ICETE Manifesto II: Call and Commitment to the Renewal of Theological Education (Evangelical review of theology, 2023)
The article focuses on the introduction of ICETE Manifesto II, which outlines the call and commitments for the renewal of theological education. The manifesto emphasizes the purpose, content, and form of theological education, the importance of contextualization and global conversations, the need for outcome-oriented curricula and integrative learning processes, the scope of theological education in various spheres of life, and the significance of leadership and organizational structures.